Financial Performance is Associated With PPE Shortages in Chain-Affiliated Nursing Homes During the COVID-19 Pandemic: A Longitudinal Study - Yejin Kang MPH; Samuel V. David PT; John R. Bowblis PhD; Orna Intrator PhD; Brian Downer PhD; Chih-Ying Li PhD, OTR; James S. Goodwin MD; Huiwen Xu PhD (SAGE Publishing, 2023)
Many nursing homes operated at thin profit margins prior to the COVID-19 pandemic. This study examines the role of nursing homes' financial performance and chain affiliation in shortages of personal protection equipment (PPE) during the first year of the COVID-19 pandemic. We constructed a longitudinal file of 79 868 nursing home-week observations from 10 872 unique facilities. We found that a positive profit margin was associated with a 21.0% lower probability of reporting PPE shortages in chain-affiliated nursing homes, but not in non-chain nursing homes. Having adequate financial resources may help nursing homes address future emergencies, especially those affiliated with a multi-facility chain.